Massive cutaneous myiasis mimicking brain invasion. Case report and literature review (2016)
ABSTRACTMyiasis is the infestation or parasitism of the humans or animals host´s living or necrotic tissues and organs caused by larvae of Diptera, it is endemic to tropical and subtropical regions of America and Africa; more common in men than in women and in middle and old age, looking mainly affected patients with any medical or anatomical predisposing condition. The differential diagnosis includes common diseases such as cellulitis and furunculosis; treatment is aimed at complete removal of larvae, either by manual pressure or surgical and most feared complication is secondary infection. A review of the literature in the context of the presentation of a clinical case of massive cutaneous myiasis, which mimicked brain invasion and required prolonged hospitalization under medical-surgical treatment is performed; in order to highlight the importance of knowledge of the disease, its evolution and emphasize on the most significant epidemiological, clinical, surgical and preventive aspects on this entity. In conclusion we assume that the myiasis is a preventable disease with a goodprognosis for cure, if detected and diagnosed early. MÉD.UIS. 2016;29(2):145-53.Keywords: Myiasis. Díptera. Larvae. Brain diseases. Treatment.